Medicinal Leech Therapy as an Alternative Treatment for Vein Problems after Free Flap Surgery: A Case Report - Soengkar, Amru; Kusumastuti, Nadia; K., Dewi Haryanti; Adib, Affan (Jurnal Plastik Rekonstruksi, 2012)
Background: Venous stasis due to vein thrombosis is a complication after microsurgical procedure which if left untreated, may ultimately lead to flap failure. Medicinal leech has been useful as a conservative treatment to overcome venous stasis in cases where it is not possible to perform salvaging procedure.Patients and Methods: A 28-year-old female who suffered from a defect on the right heel following traffic accident. The patient was initially treated by performing sural flap to cover the heel defect, but was unsuccessful. Next reconstruction was done with free radial forearm flap, however in the early postoperative period vein compromise was seen which was caused by vein thrombosis. Even though heparinization therapy was immediately begun, the result was still unsatisfactory, so medicinal leech therapy was performed to prevent loss of entire flap tissue.Results: Leeches turned out to be bulging due to sucking process on the congested venous. The sucking result on this patient was satisfactory.Summary: This study shows that free tissue transfers with surgically unsalvageable venous obstruction can be helped by leech therapy protocol.